Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445486
|View full text |Cite
|
Sign up to set email alerts
|

Reward Seeking or Loss Aversion?

Abstract: According to psychology research, emotional induction has positive implications in many domains such as therapy and education. Our aim in this paper was to manipulate the Regulatory Focus Theory to assess its impact on the induction of regulatory focus related emotions in children in a pretend play scenario with a social robot. The Regulatory Focus Theory suggests that people follow one of two paradigms while attempting to achieve a goal; by seeking gains (promotion focus -associated with feelings of happiness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A Wilcoxon signed-rank nonparametric test revealed that children show significantly more expressions of happiness in terms of smile (W 199, p 0.013, M 9.45, SD 12.92) and joy (W 216, p 0.03, M 7.52, SD 12.04) in the promotionfocused condition than in the prevention-focused condition (Elgarf et al, 2021).…”
Section: Manipulation Checkmentioning
confidence: 95%
See 2 more Smart Citations
“…A Wilcoxon signed-rank nonparametric test revealed that children show significantly more expressions of happiness in terms of smile (W 199, p 0.013, M 9.45, SD 12.92) and joy (W 216, p 0.03, M 7.52, SD 12.04) in the promotionfocused condition than in the prevention-focused condition (Elgarf et al, 2021).…”
Section: Manipulation Checkmentioning
confidence: 95%
“…Results suggest that children were more socially engaged in the promotion-focused condition than in the prevention-focused condition. Data analysis, procedures, and methods for the analysis of happiness and social engagement are explained in detail in the study by Elgarf et al (2021).…”
Section: Manipulation Checkmentioning
confidence: 99%
See 1 more Smart Citation
“…Agents (e.g robots and virtual characters) have long been used for educational purposes. A typical application and entertaining activity of using agents for education is storytelling used for helping children learn languages, develop their social skills and stimulate their creativity [23,22,13,35,12]. Previous literature has been in favor of structuring educational activities between a robot and a human user in a collaborative manner to render the activity more engaging and maximise the user's learning performance [1,2,20].…”
Section: Collaborative Storytelling With Agentsmentioning
confidence: 99%